The Realization of the “Ardhana Paramitha” Gown Design Representation the Goddess Concept - Handayani, Suci Meta; Kusumastuti, Adhi (Journal of Creativity Student, 2025)
This study aimed to develop the “Ardhana Paramitha” gown as a representation of a goddess concept articulated through fashion aesthetics. The research adopted a Research and Development (R&D) approach employing the ADDIE model, implemented systematically through the stages of analysis, design, development, implementation, and evaluation to produce a technically feasible fashion product. Data were collected through a feasibility assessment by three expert panellists who evaluated the gown using six indicators: design, size, aesthetic, construction technique, fashion performance, and peculiarity of fashion. The findings indicated that the gown satisfied the categories from “Feasible” to “Highly Feasible” across all indicators, with the highest scores in aesthetics, distinctiveness, and design. The realization of the “Ardhana Paramitha” gown successfully interpreted the character of a goddess figure and contributes to the advancement of creative fashion scholarship through the integration of mythology themes into contemporary fashion design practice.